Motive of «ennui de vivre» in the poetry of P. Verlaine and I. Annensky: comparative aspect - Онопрієнко, Анастасія Дмитрівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
This article deals with the specifics of realization of motive of «melancholy of life» («ennui de vivre») in P. Verlaine’s and I. Annensky's poetry. The attention is paid to artistic methods of implementation of motive of «melancholy of life» at the formal and substantial levels of works. The mechanism of functionning of motive of «ennui de vivre» n the framework of impressionist poetics of  P. Verlaine and I. Annensky is investigated. On the ground of analysis of poetic texts of French and Russian authors in the comparative aspect it is made the conclusion about the features of influence of P. Verlaine’s poetics on I. Annensky's poetry. The typological similarities and differences in the functioning of the motif are determined.